PRINCIPLES OF TRAINING MANAGEMENT PERSONNEL FOR PRESCHOOL EDUCATIONAL ORGANIZATIONS IN THE HIGHER EDUCATION SYSTEM - Umarova Mukaddas Mukhtarovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, future leaders who will take an active part in the management of preschool educational organizations in the process of socio-economic, spiritual and educational transformations, the development of market relations, the development of science, technology, technology and the rapid exchange of information in the republic talk about preparation.